Patterns of Prevalence of Multiple Sensory Impairments Among Community-dwelling Older Adults. Issue 10 (5th October 2021) - Armstrong, Nicole M; Wang, Hang; E, Jian-Yu; Lin, Frank R; Abraham, Alison G; Ramulu, Pradeep; Resnick, Susan M; Tian, Qu; Simonsick, Eleanor; Gross, Alden L; Schrack, Jennifer A; Ferrucci, Luigi; et al.
Abstract: Background: Much is known about individual sensory deficits among older adults, but there is a dearth of information about the prevalence of multiple concurrent sensory deficits in this population. Methods: We evaluated the prevalence of individual and multiple sensory impairments at the most recent clinic visit among participants aged 24 years and older in the Baltimore Longitudinal Study of Aging (BLSA) (hearing, vision, olfaction, proprioception, and vestibular function) and Atherosclerosis Risk in Communities Study (ARIC) (hearing, vision, olfaction). We compared observed prevalence of multiple sensory impairments with expected prevalence based on compounded probabilities of multiple impairments using Fisher Exact Tests. Also, we evaluated the comparability of different measures used between these two studies. Results: In both studies, the prevalence of each individual sensory impairment was common (>10%), and higher with older age, and the most common pattern of co-occurring sensory impairments was hearing and visual impairments (17.4% [BLSA]; 50.2% [ARIC]). In BLSA, the pattern that differed the most between observed and expected prevalence was combined hearing, vision, and olfactory impairments (observed 5.2% vs 1.4% expected, p = .01). In ARIC, this difference was much smaller (observed 8.1% vs 7.2% expected, p = .49). Conclusions: Although concurrent hearing and vision impairments were the most common co-occurring deficits, combined hearing, vision, and olfactory impairments are most likely to co-occur above chance, especially at older ages.